Multilateralization of Promotionof Democracy in Latin America:an Analysis Through the EnglishSchool Tradition - Barros, Marinana Andrade (Conjuntura internacional, 2015)
The article aims to discuss the adequacy of using the English School tradition as a theoreticalapproach to analyze the promotion of democracy in Latin America. We conclude that itis suitable because of the emphasis on internationally shared values and norms, the acceptanceof change and of methodological pluralism.